The effect of combined temperature-pressure treatments on pepper (Capsicum annuum) pectin methylesterase in model systems - Castro, S. (2012)
At atmospheric pressure, purified pepper PME starts to inactivate at temperatures higher than 54°C. But when mild temperaturelhigh-pressure treatments are applied (T254"C, P<300MPa), an antagonistic effect of pressure and temperature is observed. Pressure seems to wield a protective effect on heat inactivation. Within the thermallhigh-pressure domain investigated, maximal pepper PME activity in the presence of pectin was observed at 200MPaI55"C. At temperatures lower than 50°C, PME activity decreased with pressure; while at temperatures higher than 50°C, there was an enhancement of the pressure effect from 0.1-200MPa, followed by a decrease for higher pressures.